Wu ching: Shih ching. Shu ching. I ching. Li chi. Ch'un ch'iu (Hua Ching T'ang, Wen Hsün Lou, and Fu Wen T'ang, 1842)
1-4. The Book of odes. -- 5-6. The Book of history. -- 7-8. The Book of changes. -- 10-14. The Book of rites. -- 16. The Book of annals.